2010
DOI: 10.1186/1471-2407-10-375
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of angiogenesis resulting from cooperation between macrophages and MDA-MB-231 breast cancer cells: proposed molecular mechanism and effect of tetrathiomolybdate

Abstract: BackgroundInfiltration by macrophages (Mφ) indicates a poor prognosis in breast cancers, in particular by inducing angiogenesis. Our study aimed 1) to investigate the mechanism by which cooperation between Mφ and aggressive breast cancer cells (MDA-MB-231) induces angiogenesis; 2) to examine the effect of tetrathiomolybdate (TM) on this angiogenic activity.MethodsMφ coincubated with MDA-MB-231 were used as a model to mimic the inflammatory microenvironment. Angiogenesis induced by the culture media was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 56 publications
(47 reference statements)
4
25
0
Order By: Relevance
“…This work provides evidence for a synergistic interaction between macrophages and tumour cells during cell migration in vivo and could explain, at least in part, the increased tendency of basal-like BCs, which overexpress EGF receptor, to be more node negative and show haematogenous rather than lymphatic dissemination to viscera and bone [60,61]. Macrophages are well known to produce interleukin-10 and angiogenic factors [62]. Within the hypoxic environment, growth factors that promote angiogenesis and lymphangiogenesis are up-regulated and secreted by malignant cells [63] and serve as chemo-attractants for macrophages.…”
Section: Tumour Cell Invasiveness Tumour Microenvironment and LVImentioning
confidence: 99%
“…This work provides evidence for a synergistic interaction between macrophages and tumour cells during cell migration in vivo and could explain, at least in part, the increased tendency of basal-like BCs, which overexpress EGF receptor, to be more node negative and show haematogenous rather than lymphatic dissemination to viscera and bone [60,61]. Macrophages are well known to produce interleukin-10 and angiogenic factors [62]. Within the hypoxic environment, growth factors that promote angiogenesis and lymphangiogenesis are up-regulated and secreted by malignant cells [63] and serve as chemo-attractants for macrophages.…”
Section: Tumour Cell Invasiveness Tumour Microenvironment and LVImentioning
confidence: 99%
“…VEGF and angiopoietins) and metallo-proteases [252,253]. It has been shown that TM-induced copper starvation in a co-culture of malignant breast cancer cells and macrophages does not interfere with the local release of angiogenic cytokines, but compromises downstream angiogenic-dependent cell signalling [253]. An in vitro study on RAW264.7 macrophage cell cultures exposed to hypoxia, a condition of a real tumour context, showed relevant changes in the expression and activity of cell copper transport proteins, reflecting a higher delivery of the metal to ceruloplasmin [134], and an obvious elevation of blood-circulating copper in a bioavailable form.…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…Copper actively contributes the inflammatory cross-talk between cancer cells and tumour-recruited macrophages which locally stimulate angiogenesis by releasing a wide array of pro-angiogenic factors (e.g. VEGF and angiopoietins) and metallo-proteases [252,253]. It has been shown that TM-induced copper starvation in a co-culture of malignant breast cancer cells and macrophages does not interfere with the local release of angiogenic cytokines, but compromises downstream angiogenic-dependent cell signalling [253].…”
Section: Copper and Angiogenic Diseasesmentioning
confidence: 99%
“…TAMs are well-known to produce Interleukin-10 and angiogenic factors [61], and they aggregate nearby necrotic and hypoxic areas of the tumour microenvironment [62]. Hence, and under this hypoxic environment, growth factors that promote blood and lymph neovascularization are upregulated and secreted by the malignant cells.…”
Section: The Tumour Microenvironment and Metastasismentioning
confidence: 99%